Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/00224499.2020.1827217
|View full text |Cite
|
Sign up to set email alerts
|

Social Media, Marijuana and Sex: An Exploratory Study of Adolescents’ Intentions to Use and College Students’ Use of Marijuana

Abstract: Recreational marijuana continues to be legalized in U.S. states, with popular media discussing connections between cannabis and the facilitation of sexual activity. We conducted two surveys with adolescents and college students in Washington state to examine the role of viewing social media and pro-marijuana content on sex-related marijuana expectancies and intentions to use. In Study 1, among adolescents (N = 350), we found connections between social media use, exposure to pro-marijuana content, and sexrelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…examination of specific perceptions of the content within the posts. Adolescents' and college students' perceptions of cannabis content as positively portraying use and relationship facilitation are associated with intentions to use cannabis, beyond time spent on social media [17]. Among college students, increased positive perceptions of cannabis content on social media are also associated with frequency of use indirectly through intentions [17,21].…”
Section: Perceptions Mediate the Relationship Between Exposure And Ex...mentioning
confidence: 97%
See 3 more Smart Citations
“…examination of specific perceptions of the content within the posts. Adolescents' and college students' perceptions of cannabis content as positively portraying use and relationship facilitation are associated with intentions to use cannabis, beyond time spent on social media [17]. Among college students, increased positive perceptions of cannabis content on social media are also associated with frequency of use indirectly through intentions [17,21].…”
Section: Perceptions Mediate the Relationship Between Exposure And Ex...mentioning
confidence: 97%
“…Adolescents' and college students' perceptions of cannabis content as positively portraying use and relationship facilitation are associated with intentions to use cannabis, beyond time spent on social media [17]. Among college students, increased positive perceptions of cannabis content on social media are also associated with frequency of use indirectly through intentions [17,21]. This finding that perceptions of media content is associated with outcomes is also supported in other research; sex-related alcohol expectancies, which are beliefs about how alcohol can influence sexual activities and experiences, are impacted by exposure to sexualised alcohol ads through perceptions that the ads suggest alcohol facilitated sex [22].…”
Section: Perceptions Mediate the Relationship Between Exposure And Ex...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found different associations with tanning behaviors based on specific platforms [6]. A greater understanding of the specific content to which young people are exposed could help further explain effects beyond mere exposure, as previous research in other topic areas has found that perceptions of media messages may be influential among young people [66,67]. Future research also should continue to explore the relationship between social media and tanning behaviors among young women to further parse out the mechanisms through which effects occur and to continue to bolster prevention efforts.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%